2011
DOI: 10.1007/s00421-011-2004-2
|View full text |Cite
|
Sign up to set email alerts
|

Does 20-min arm crank ergometer exercise increase plasma interleukin-6 in individuals with cervical spinal cord injury?

Abstract: Interleukin-6 (IL-6) is produced by contracting skeletal muscles and then released into the circulation and considered to mediate the health benefits of exercise against chronic diseases. Individuals with spinal cord injury (SCI) are reported to be at higher risk of developing metabolic diseases. We investigated the IL-6 responses to 20-min arm crank ergometer exercise at 60% of maximum oxygen consumption in eight trained individuals with cervical SCI (CSCI) between C6 and C7, and eight able-bodied trained hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 30 publications
5
34
3
Order By: Relevance
“…Future research using interventions at a range of immersion temperatures may elucidate the minimum "critical" temperature elevation needed to induce a cytokine response. The increases in IL-6 and IL-1ra in CSCI following hot water immersion differ from earlier exercise interventions, where no acute cytokine elevations in the acute post-exercise phase were found in similar populations (Kouda et al 2012;Paulson et al 2013), whereas up to 128-fold increases in IL-6 following the longest and most strenuous forms of exercise are found in the AB population (Pedersen and Febbraio 2008). As our present results show that elevated core temperature seems to independently induce a cytokine response, it seems possible that the reduced active muscle mass in CSCI does not allow for sufficient core temperature elevations during exercise to mount a cytokine response.…”
Section: Markers Of Inflammationcontrasting
confidence: 65%
See 2 more Smart Citations
“…Future research using interventions at a range of immersion temperatures may elucidate the minimum "critical" temperature elevation needed to induce a cytokine response. The increases in IL-6 and IL-1ra in CSCI following hot water immersion differ from earlier exercise interventions, where no acute cytokine elevations in the acute post-exercise phase were found in similar populations (Kouda et al 2012;Paulson et al 2013), whereas up to 128-fold increases in IL-6 following the longest and most strenuous forms of exercise are found in the AB population (Pedersen and Febbraio 2008). As our present results show that elevated core temperature seems to independently induce a cytokine response, it seems possible that the reduced active muscle mass in CSCI does not allow for sufficient core temperature elevations during exercise to mount a cytokine response.…”
Section: Markers Of Inflammationcontrasting
confidence: 65%
“…It is also possible that the Ca 2+ dependent pathways during muscle contraction that induce a cytokine response (Pedersen and Febbraio 2008) are not sufficiently activated in CSCI as a result of the drastically reduced active muscle mass. Additionally, as catecholamines independently induce a cytokine response (Steensberg et al 2001), the blunted catecholamine response in CSCI following exercise interventions (Banno et al 2012;Kouda et al 2012;Paulson et al 2013) may explain the blunted exercise response on cytokine concentrations. The secretion of anti-inflammatory cytokines following exercise may therefore be reduced in CSCI, blunting the anti-inflammatory effects of exercise as described by Gleeson et al (2011).…”
Section: Markers Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Performance parameters (distance and speed of propulsion) Several different types of exercise lasting 20 min, including arm ergometer, 15 handcycling 16 or wheelchair, 1 have been conducted to evaluate the performance of people with SCI.…”
Section: Samplementioning
confidence: 99%
“…1 Based on these two factors, we hypothesized that because of the relatively small muscle volume in the CSCI group, as compared with the SCI group, exercise is not likely to increase IL-6 during exercise. Actually, Kouda et al 6 reported that 20-min arm exercise at 60% of VO 2 max in individuals with CSCI did not increase IL-6.…”
Section: Introductionmentioning
confidence: 98%